2021
DOI: 10.1186/s12879-020-05759-0
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne botulism presenting as small bowel obstruction: a case report

Abstract: Background Small bowel obstruction is one of the leading reasons for accessing to the Emergency Department. Food poisoning from Clostridium botulinum has emerged as a very rare potential cause of small bowel obstruction. The relevance of this case report regards the subtle onset of pathognomonic neurological symptoms, which can delay diagnosis and subsequent life-saving treatment. Case presentation A 24-year-old man came to our Emergency Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Gastrointestinal symptoms are common in food botulism (nausea, vomiting, abdominal pain, diarrhea, dry mouth) and may precede neurological syndromes [38]. It has been found that botulism can lead to small bowel obstruction and, if misdiagnosed, can lead to rapid clinical deterioration [39]. Botulinum toxin (BTX) is used in medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Gastrointestinal symptoms are common in food botulism (nausea, vomiting, abdominal pain, diarrhea, dry mouth) and may precede neurological syndromes [38]. It has been found that botulism can lead to small bowel obstruction and, if misdiagnosed, can lead to rapid clinical deterioration [39]. Botulinum toxin (BTX) is used in medicine.…”
Section: Resultsmentioning
confidence: 99%